The Integrasi Teknologi Gamifikasi dalam Pembelajaran Bahasa Inggris ; Dampak terhadap Keterlibatan dan Prestasi Mahasiswa Non-Bahasa Inggris - Said, Rahmat; Kairawan, Kairawan (EduPsyCouns: Journal of Education, Psychology and Counseling, 2024)
The objective of this research is to integrate the Quizizz application as an innovation in English teaching, particularly to improve the motivation and academic achievement of non-English students in reading and writing skills. Quizizz provides interactive and fun quiz games, allowing for adaptation of learning content according to students’ needs and skill levels. This study employs a quantitative research design with a quasi-experimental approach. The sample of this study consists of 32 samples in an experimental class and 34 students in the control class who are 4th-semester students of PGSD majoring at Universitas Muhammadiyah Enrekang during the 2023–2024 academic year. Data were collected using pretest and post-test, as well as analyzed through SPSS to test the validity and reliability of the research instrument and hypothesis. The results showed that the use of Quizizz application significantly affected English academic achievement improvement among students. The majority of the students showed increased motivation and performance in their learning, which yielded a positive impact on their grades.